Aplicação de ferramentas quimiométricas no desenvolvimento e caracterização de produtos alimentícios contendo Salvia hispânica, L - Souza, Aloisio Henrique Pereira de (2015)
The burgers are commonly produced from low cost commercial beef cuts along with fat typically subcutaneous tissue origin, and which has a direct influence on the majority lipid composition of the final product. Lipids are also of great importance, as they are a source of energy and essential fatty acids, and act in the transport of fat-soluble vitamins. However, animal lipids have high levels of cholesterol and saturated fatty acids, which are associated with many types of cardiovascular and coronary heart disease, and obesity risk. Thus, the use of vegetable lipid sources could result in products which are considered healthier. In this context, it highlights the use of chia (Salvia hipanica, L.) is considered a grain source of alpha linolenic fatty acid. In the development of food products it is necessary to change the various ingredients and processing parameters. The factorial design is a dynamic tool, which enables to make a small number of experiments, to evaluate multiple variables simultaneously, their effects, more reliable results, in an interactive process of addition or removal tests on the model, to enable the selection of the main variables and presentation of mathematical models with findings from qualitative results. Categorical factorial designs have the characteristic extracting information about types of ingredients, processes and parameters that cannot be varied as in the numeric variables. The objective of this thesis was the application of chemometric methods to investigate the influence of numerical and categorical factors in the development of bovine burgers processing formulations and vegetables containing co-product or wholemeal chia on the fatty acid composition, lipid oxidation, proximal and features nutrition. A full factorial design 22 (two factors in two levels) in duplicate were performed to investigate the influence of factors:% of textured soybean protein (TSP) and partially defatted flour chia (FDC) in partial replacement of the beef mixture and pork bacon on burgers. Composition analyzes were made in fatty acids, lipid oxidation and proximal being proposed mathematical models with the answers, principal component analysis and evaluation of the desirability function. Factorial design application categorical in developing vegetable burger as fatty acid source of omega-3 and get a better formulation by optimizing the experiment. For this we investigated the influence of two sources of omega-3, emulsifiers / binders and the effect of processing on the composition of fatty acids. The percentage of PTS and FDC factors were significant, and the increase in these values, helped to improve the fatty acid composition, crude protein and gray. The principal component analysis distinguished the samples with greater chia content through CP1 and CP2. There have been some restrictions on the responses to the desirability analysis. In this analysis the higher level of PTS and FDC was characterized as the optimal point of highest desirability. All the main and interaction effects were significant. In the hierarchical analysis was the formation of two well-defined groups, one with creaky and one with flaxseed, both having xanthan / carboxymethylcellulose and without cooking gum. The fatty acid composition in the tests was equal and there was a significant variation between the formulations. In models the main effect emulsifier and interaction with the three evaluated factors showed the highest percentage of contribution. In this analysis the product containing chia as a source of omega-3, xanthan gum / carboxymethylcellulose as an emulsifier in baked hamburger was characterized as the optimal point of highest desirability. The experimental design used in the burger showed that the increase of the studied factors contributed to improving the fatty acid composition, protein, ash and the nutritional quality of the product. The principal component analysis distinguished the samples with greater chia content through CP1 and CP2. The desirability of analyzing the top-level PTS and FDC was characterized as the optimum point there is no need to do another experimental point. The addition of the coproduct chia is an alternative to increase the alpha linolenic content and more nutritionally balanced foods. The use of vegetables, especially the chia is an alternative in the development of a nutritionally balanced food, with a view to applying various chemometric tools from the selection of ingredients, processing and characterization of vegetal hamburger. Effect of the addition of chia's by-product on the composition of fatty acids in hamburgers through chemometric methods.